Leadership agility in a VUCA world: a systematic review, conceptual insights, and research directions - Syamsir Syamsir; Nika Saputra; Rizki Afri Mulia (Cogent Business & Management)
This study explores leadership responsiveness within the VUCA framework through a systematic review of 116 Scopus-indexed research papers using the PRISMA technique. Unlike previous studies, this research incorporates bibliometric analysis and thematic synthesis to provide a structured understanding of leadership agility. Additionally, it examines the transition from VUCA to BANI, offering a more contemporary perspective. This study develops a conceptual model linking agile leadership with its contextual, organizational, and individual drivers. Findings indicate that digital transformation, globalization, and post-pandemic shifts significantly shape leadership agility. Mediating factors such as dynamic capabilities, systems thinking, and change management enhance agility, driving sustainable performance, organizational resilience, and employee adaptability. Bibliometric analysis highlights emerging research trends, while thematic synthesis structures leadership agility’s strategic adaptability. While this study is constrained to literature cataloged in Scopus, potential selection bias may arise due to excluding non-open-access articles. Nevertheless, the findings offer practical insights for organizations seeking to enhance leadership agility in uncertain environments. This study provides actionable strategies for business leaders and HR professionals, including leveraging technology, fostering a learning-oriented culture, and improving cognitive flexibility. This study bridges theoretical gaps and outlines future research directions, emphasizing empirical validation across various sectors and cultures.